Illness as metaphor in news articles: an application of metaphor detection - Mishra, Spriha Bankata (Nanyang Technological University, 2022)
Mental disorders such as schizophrenia and bipolar disorder often have stigma and prejudice attached to them. Public perception of such disorders is generally negative, and these perceptions lead to debilitating effects on the diagnosis and treatment of patients. One common form of expression these stigmatising beliefs take is through metaphor. Metaphors involve mapping an abstract domain to another, often more concrete one. Metaphorical references to mental disorders are often used to evoke negative feelings and associations. Such references are present in various forms of media and reflect cognitive beliefs about these disorders. This project examines the domain of news articles to collate metaphorical references to schizophrenia and bipolar disorder by leveraging a state-of-the-art metaphor detection model. Thus, this project studies one possible application of the powerful computational models for metaphor detection evolving today. News articles from various American and Singaporean publications are investigated for metaphorical references to the mental disorders and the implications of these references are discussed. Metaphorical usage of these terms is impossible to fully eradicate, but bringing attention to the problem is a crucial first step. Keywords: Metaphor Detection, News Articles, Illness as Metaphor, Schizophrenia, Bipolar Disorder